Evaluation of specific occupational asthma risks in a community-based study with special reference to single and multiple exposures - Zock, Jan-Paul; Cavallé, Núria; Kromhout, Hans; Kennedy, Susan M; Sunyer, Jordi; Jaén, Ángeles; Muniozguren, Nerea; Payo, Félix; Almar, Enrique; Sánchez, José L; Antó, Josep M; Kogevinas, Manolis (Journal of exposure analysis and environmental epidemiology, 2004)
Objectives: To compare two job exposure matrices (JEMs) for the evaluation of asthma risks related to specific occupational exposures in a community-based study. Methods : A questionnaire on self-reported asthma, respiratory symptoms and current occupation was sent to the participants of the European Community Respiratory Health Survey in five areas in Spain. Both an asthma-specific JEM, including expert judgment steps and a general JEM, were applied to occupational codes. Risks of current asthma symptoms and wheeze in the last year associated with the obtained exposure estimates were evaluated. Correlations between specific exposures were investigated using explanatory factor analysis. Results : Occupational exposures to the high-molecular-weight (MW) agents flour dust, enzymes, mites and animal-derived proteins as obtained by the asthma-specific JEM were positively associated with asthma outcomes. The effect of additional expert judgment steps was limited. High exposures to biological dust assessed by the general JEM without expert judgment was also associated with asthma. Many of the exposed individuals worked in environments with multiple exposures. Conclusions : Asthma risks associated with occupational exposures to specific high-MW agents could be identified from a population-based study using an asthma-specific JEM. Application of JEMs can be a useful tool to estimate asthma risks attributable to specific occupational exposures in the general population. However, these specific exposure risks should be interpreted in connection with the whole of concomitant exposures constituting the work environment.